A review on the application of cohesive zone model in hydraulic fracturing. Issue 1 (1st January 2023) - Li, X J; Zhao, H F; Xu, K Q; He, Y L; Wang, C W; Yao, W J
Abstract: Hydraulic fracturing is an effective measure to increase production and injection and blockage removal in oil and gas field development. Accurate prediction of fracture morphologies is the key to the optimized design of hydraulic fracturing. The cohesive zone model (CZM) has been widely used in the numerical simulation of fracture initiation and propagation during hydraulic fracturing. The fractures formed by the numerical simulation vary significantly with different CZMs. In the current numerical simulation, the CZM generally adopts the bilinear model, which is more suitable for describing brittle fracture, while rocks are quasi-brittle materials and have nonlinear CZMs. This deviation should be corrected. Moreover, the CZM parameters are generally determined based on experience, without a reliable basis and standard determination method. This article focused on the CZM, systematically introduced its concept and classification, and clarified the correlation between the types of CZMs and the brittleness, quasi-brittleness, and ductility of rock fracture. The application of CZM in hydraulic fracturing was reviewed, and the existing problems, corresponding countermeasures and future research trends were presented. An integrated method of combining laboratory experiments, data mining and numerical simulation to determine the CZMs of mode I, mode II, and I/II mixed mode cohesive cracks was proposed.